Handbook of nanoscale optics and electronics - Wiederrecht, Gary P. (Elsevier, 2010)
With the increasing demand for smaller, faster, and more highly integrated optical and electronic devices, as well as extremely sensitive detectors for biomedical and environmental applications, a field called nano-optics or nano-photonics/electronics is emerging - studying the many promising optical properties of nanostructures. Like nanotechnology itself, it is a rapidly evolving and changing field - but because of strong research activity in optical communication and related devices, combined with the intensive work on nanotechnology, nano-optics is shaping up fast to be a field with a p.